The Socialization and its role in shaping the identity of the individual (In shadow of the globalization bet) - ZEGHINA, Naoual (Social Sciences Journal, 2019)
Abstract: The présent study aims to identify the role of socialization in shaping the identity of the individual in the context of globalization, by highlighting the various organizations supervising the process, and highlight the mechanisms of the formation of identity. The study concluded that socialization keeps the entity of society and its cohesion, through the realization of its goals in the formation of the social profile of the individual, to be consistent and belong to the community, The formation of identity and conservation, in the framework of globalization, it is through the integration of the roles of organizations responsible for socialization and supervision process and monitor the family